2010
DOI: 10.1097/paf.0b013e3181e040d4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Diagnosis and Subsequent Autopsy Findings in Medical Malpractice

Abstract: The rate of diagnostic error has not declined over the last 30 years despite the improvement in diagnosis methods. Today, the probability to encounter a major diagnostic change in autopsy is still high. The special autopsy that provides clinicians the necessary feedback is performed seldom in our country. This study has been started upon the claim that the malpractice cases in scope of forensic cases could be a very useful database. About 525 cases with faulty medical application that resulted in death have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…The authors demonstrate in the present study an overall concordance of 55% between clinical diagnoses and the causes of death established by the forensic pathologists. These results are consistent with the results of other similar studies, including Pakis, who found a concordance rate of 49.1% in cases where clinicians were accused of malpractice . A missed diagnosis or undiagnosed case refers to the circumstance where no diagnosis is made clinically until postmortem examination.…”
Section: Discussionsupporting
confidence: 91%
“…The authors demonstrate in the present study an overall concordance of 55% between clinical diagnoses and the causes of death established by the forensic pathologists. These results are consistent with the results of other similar studies, including Pakis, who found a concordance rate of 49.1% in cases where clinicians were accused of malpractice . A missed diagnosis or undiagnosed case refers to the circumstance where no diagnosis is made clinically until postmortem examination.…”
Section: Discussionsupporting
confidence: 91%
“…In the same time, autopsy represents a useful audit tool in clinical settings [2,[7][8][9][10][11][12][13], which contributes in a significant way to the progress of medicine and improvement of current medical practice, as well as to the medical education in universities [14,15].…”
Section: Abstract: Autopsy Chemistry Reactions Diagnosis Forensicsmentioning
confidence: 99%
“…El interés es clínico, por un lado, pues permite profundizar en el conocimiento de aspectos técnicos mejorables del procedimiento realizado 22 . Por otro, facilita el descubrimiento de factores de riesgo, lo que mejora la gestión de los mismos en casos futuros 23 .…”
Section: Necesidad De La Autopsiaunclassified